Analysis of Prognostic Factors Affecting the Brain Metastases Free Survival and Survival After Brain Metastases in Breast Cancer - Xiao, Weikai; Li, Xuerui; Yang, Anli; Chen, Bo; Zheng, Shaoquan; Zhang, Guochun; Deng, Wenju; Liao, Ning (Frontiers in Oncology, 2020)
Abstract This study aimed to analyze the factors affecting brain metastases free survival (BMFS)and the survival after brain metastases (SABM).The data of 215 patients with breast cancer brain metastases (BCBM) in Sun Yat-sen University Cancer Center from January 2000 to August 2017 were retrospectively analyzed. The clinicopathological features of BCBM were analyzed, and their effects on BMFS and SABM were analyzed by univariate and multivariate COX regression. Finally, it was analyzed whether the receptor status of the brain metastases and the primary lesions were consistent.The median age of the entire cohort was 46 years old. The median BMFS, SABM and overall survival were 31, 9 and 44.2 months, respectively. Clinical stage, molecular subtypes and bone metastasis were independent prognostic factors affecting BMFS. TNM stage IV (HR, 4.99 [95% CI, 2.13-11.7] and triple negative subtype (HR, 2.06 [95% CI, 1.35--3.14]) was significantly associated with shorter BMFS, but the presence of bone metastases (HR, 0.63 [95% CI, 0.45--0.88]) was a favorable factor for BMFS. Molecular subtypes, resection of BCBM and whole brain radiotherapy (WBRT) were independent factors for SABM. The triple negative subtype (HR, 2.02[95% CI, 1.12-3.64]) was significantly associated with shorter SABM. However, resection of BCBM (HR, 0.31 [95% CI, 0.15--0.65]) and WBRT (HR, 0.57 [95% CI, 0.35--0.93]) were independent factors in improving SABM. The conversion rate of ER was 11.1%, PR was 29.6%, and HER2 was 3.7% between paired breast cancer and brain metastases. BMFS and SABM have different influencing factors. Resection of BCBM and WBRT can significantly improve SABM. The frequency of HER2 status changes between the paired BCBM and the primary lesions is low.